Comparison of effects of bronchial blocker and double-lumen endobronchial tube in video-assisted thoracoscopic surgery: based on propensity score matching analysis - OU Yi; SHAO Yu; HAN Jia; YANG Yilin; LIAO Boyong (Yixue xinzhi zazhi)
Objective To compare the application effects of bronchial blocker (BB) and double- lumen endobronchial tube (DLT) in video-assisted thoracoscopic surgery (VATS).Methods A retrospective analysis was conducted on the clinical data of patients who underwent VATS in Mianzhu People's Hospital from January 2022 to December 2024. According to the catheter placement method, patients were divided into BB and DLT groups. After using propensity score matching (PSM) in a 1:1 ratio to balance the baseline data of two groups, the differences in surgical monitoring indicators, intubation positioning time, intubation time, lung collapse quality, and adverse reactions between the two groups were compared.Results A total of 334 VATS patients were included, including 168 in the DLT group and 166 in the BB group. After PSM, there were 120 cases in each group. There was no statistically significant difference in heart rate, blood oxygen saturation, systolic blood pressure, diastolic blood pressure, end expiratory carbon dioxide pressure, and peak airway pressure between the two groups at the beginning of surgery and 0.5 hours after surgery (P>0.05). There was no significant difference in intubation positioning time between the two groups (P>0.05). The intubation time of the BB group was significantly shorter than that of the DLT group, and the proportion of good lung collapse quality in the DLT group was higher than that in the BB group (P﹤0.05). In terms of adverse reactions, there was no significant difference in the incidence of hoarseness and airway injury between the two groups 24 hours after surgery (P>0.05). Compared with the BB group, the incidence of moderate to severe pharyngitis in the DLT group 24 hours after surgery was higher (P ﹤0.05).Conclusion Both BB and DLT can provide safe anesthesia management during VATS. The two devices have their own advantages and disadvantages in terms of intubation time, lung collapse quality, and postoperative pharyngalgia incidence. Clinical selection should comprehensively consider surgical needs, patient characteristics, and operator experience to achieve the optimal anesthesia management effect.